LearningRx Cognitive Training for Children and Adolescents Ages 5–18: Effects on Academic Skills, Behavior, and Cognition - Jedlicka, Edward J. (Frontiers in Education, 2017)
Cognitive training is emerging as a viable intervention for remediating cognitive skill deficits and associated academic struggles. This study investigated whether trainer-delivered cognitive training reduced parent-reported academic difficulties and oppositional behavior for school-age children with learning struggles compared to a no-contact control group. Three groups were surveyed using a standardized rating scale: parents of clients ages 5-18 who had completed the 60-hour ThinkRx cognitive training program (n = 67), parents of clients ages 5-18 who had completed the 120-hour ReadRx cognitive training with reading program (n = 53), and parents of clients ages 5-18 who completed initial testing but did not enroll in a training program (n = 58). Results indicated there were statistically significant differences overall between the intervention groups and the control group on all measures of academic difficulties. Both intervention groups saw a reduction in academic difficulty ratings following training while the control group saw an increase in academic difficulty during a comparable time interval. Differences between groups on ratings of oppositional behavior were not significant. Both intervention groups achieved statistically significant changes on objective cognitive test measures as well. Although the study is limited by lack of randomization in the sampling, the results and transfer effects are encouraging for evaluating the use of one-on-one cognitive training to enhance academic skills and behavior.